Análises macro e microestrutural e correlação com a microdureza de ligas Zn-Al solidificadas no processo de squeeze casting - Lima, Diego Ferreira de (2017)
The Squeeze Casting process is a casting process, in which the molten metal in the liquid state is solidified under pressure into mold closed by a punch. It is an economical and relatively simple technique, possessing great potential for automation and high production rates. The product is of high quality and usually has the final shape. The evolution of the microstructure during solidification depends on the process variables that can be divided into two groups, to knowing, those which describe the mold, and those which are related to the alloy. The mold is characterized by its size and geometry, temperature and thermal properties, while the alloy is characterized by its composition, temperature when cast, cooling rate, nucleation characteristics, solute transport, melt convection and heat transfer coefficients In the Metal / mold interface. During the solidification process of alloys, the most frequently observed morphology is dendritic, which can be characterized by primary (?1), secondary (?2) and tertiary (?3) dendrite spacings. Many studies analyze the influence of thermal and microstructural alloy variables Mechanical properties, showing the importance of dendritic spacings in the final properties. The objective of this work was to analyze the influence of the operational parameters of the squeeze casting process of radial solidification, as pressure and its correlation with the macrostructure and solidification microstructure, and solidification microstructure, as well as to verify how these structural changes affect the microhardness of dilute alloys of Zn-Al, used in this work Zn-2% Al alloys; Zn-3% Al and Zn-4% Al, in addition to pressures of 50, 100 and 150 MPa, as well as solidification without pressure, with pressing time of 5 s. The obtained results show in relation to the macrostructure that both the pressure variation and the variation in the composition of the alloy contributed to the refinement of the structures. As the secondary dendritic spacings generally decrease with increasing pressure, but when the concentration of solute is increased the same tends to grow.